The interaction between filaggrin mutations and hard domestic water and the risk of early‐onset atopic dermatitis. (1st August 2020) - Halling, A.‐S.; Bager, P.; Skov, L.; Zachariae, C.; Wohlfahrt, J.; Melbye, M.; Thyssen, J.P.
Abstract: Linked Article: Jabbar‐Lopez et al. Br J Dermatol 2020; 183 :285–293 .